FMRI using balanced steady-state free precession (SSFP) - Miller, K (2012)
Steady-state free precession (SSFP) is a highly-efficient MRI pulse sequence that has been a fairly recent arrival in the functional MRI realm. Several methods for using balanced SSFP to detect the BOLD signal have been proposed to date and will be discussed in this review. After a brief introduction to the general properties of SSFP, this review describes the quite different approaches of transition-band and pass-band SSFP in terms of functional contrast mechanism. It then discusses the potential advantages of these techniques, followed by their challenges and shortcomings. Finally, it gives an overview of some applications considered to date and the author's perspective on where these techniques are headed. In the spirit of this special issue, the author also includes some of the personal history underlying her own explorations in this area. © 2011 Elsevier Inc.